KARAKTERISASI PLASTIK BIODEGRADABLE NATA DE SOYA MENGGUNAKAN PLASTICIZER ASAM OLEAT - Maryati, Meri; Iryani, Iryani; Amelia, Fitri (Sainstek : Jurnal Sains dan Teknologi, 2014)
The purpose of this study were to analyze the morphology, tensile strength, power degradation and the degree of crystallinity of plastic nata de soya. This plastic using oleic acid plasticizer  with various volume 30 , 40 and 50 mL and 30 mL glycerol 3 %. Plastic morphology test using Scanning Electron Microscope ( SEM ). Tensile strength test using a test tensometer and crystallinity using X - ray diffraction instrument ( XRD ). Power degradation is determined by hoards of plastic in the soil for 10 days. The longer plastic soaked for 6 days then getting flat plastic surface morphology, the lower of  value of tensile strength is 7.87 MPa, the lower of power degradation is 23. 72 % and the higher the degree of crystallinity is 39.96 %. Key words: oleic acid, plasticizer , biodegradable  plastic, nata de soya